Differences in Students’ Problem Solving Abilities Using the Gallery Walk Method and the GeoGebra-Based Demonstration Method on the Algebraic Functions Derivatives in Class XI of SMA Negeri 1 Banda Aceh - Dika Permata Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The results of observations conducted at SMA Negeri 1 Banda Aceh, obtained that: 1) the problem-solving ability of students in solving mathematical problems is still low: 2) students have not been taught to use technology as a medium for learning mathematics, especially GeoGebra: 3) the learning methods used are still conventional. The formulation of the problem in this study are is there a difference in the problem-solving ability of students who use the Gallery Walk method and the demonstration method, both of which use Geogebra on the algebraic function derivatives in class XII F1 and XII F2 at SMA Negeri 1 Banda Aceh. This study aims to determine whether there is a difference in the problem-solving ability of students who use the Gallery Walk method and the demonstration method. This study is a quantitative study with an experimental method. The samples taken in this study were two classes, namely XII F1 as the experimental class and XII F2 as the control class. The instrument used in this study was a test (pretest-posttest). Based on the results of the analysis of test data two independent samples obtained thitung = 2, 068 and ttabel = 1.998 at the level = 0.05, then the thitung > ttabel or 2.068 > 1.998, thus H0 is rejected and Ha is accepted, which means there is a significant difference in the problem-solving abilities of students taught by the Gallery Walk method and those taught by the demonstration method on the material of algebraic derivative functions at SMA Negeri 1 Banda Aceh.